Summary and study on the curriculum reform of modern cryptography based on SPOC and flip classroom - Ning ZHANG; Shichong TAN; Xiaotong FU; Xiaogang DU; Hui LI (网络与信息安全学报)
Based on the teaching practice of modern cryptography curriculum reform in xidian university from 2015 to 2018,the practice and effect of MOOC,SPOC and flip classroom in modern cryptography were analyzed.The implementation and reform of the lab course were summarized based on the experiments with programming marathon and traditional lab course.The accomplishments and lessons of the curriculum reform were summarized and some suggestions of innovative modern cryptography education for undergraduate in the mode of “Internet +” were provided.